2017
DOI: 10.1177/0165025417741365
|View full text |Cite
|
Sign up to set email alerts
|

Mother–child conversation and social understanding in Pakistan

Abstract: Two studies are presented to examine whether and why 3–5-year-olds in Pakistan display limited social understanding. Study 1 tested 71 preschoolers on Lillard and Flavell’s (1992) test of desires, pretence and beliefs, plus two false belief tasks, and showed very limited understanding across these measures even though almost half were over 5 years old. Study 2 replicated this effect with 35 preschoolers, and also conducted home observations of mother–child interaction at two time points. It tested three compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Indeed, research has repeatedly indicated that amount of adults' mental state talk with children is positively related to their mentalizing development (Peterson & Slaughter, 2003;Ruffman et al, 2002Ruffman et al, , 2006. However, studies have revealed that adults from non-Western countries, including Pakistan, rarely engage in mental state talk with their children (Degotardi et al, 2022;Kong et al, 2023;Nawaz & Lewis, 2018;Vinden, 1996). Since the widest variation in number of family members was largely observed in the Pakistani sample, the increased adult interaction that Pakistani children would receive may be of 'lower quality' and therefore may not have benefitted the children's mentalizing development to such a degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, research has repeatedly indicated that amount of adults' mental state talk with children is positively related to their mentalizing development (Peterson & Slaughter, 2003;Ruffman et al, 2002Ruffman et al, , 2006. However, studies have revealed that adults from non-Western countries, including Pakistan, rarely engage in mental state talk with their children (Degotardi et al, 2022;Kong et al, 2023;Nawaz & Lewis, 2018;Vinden, 1996). Since the widest variation in number of family members was largely observed in the Pakistani sample, the increased adult interaction that Pakistani children would receive may be of 'lower quality' and therefore may not have benefitted the children's mentalizing development to such a degree.…”
Section: Discussionmentioning
confidence: 99%
“…Further, only two studies have investigated mentalizing development in Pakistan. Nawaz and Lewis (2018) found that Pakistani children developed ToM slower than Western children; however the study did not include a direct comparison group. Sireer (2017) similarly compared British, British-Pakistani and Pakistani children on their ToM and found that British children outperformed both other groups.…”
Section: Pakistani and British Childrenmentioning
confidence: 92%
“…MST was assessed in naturalistic observation for father and mother (Jenkins et al, 2003), for mother (e.g. Brown, Donelan-McCall, & Dunn, 1996;Nawaz & Lewis, 2018), free play (Degotardi & Torr, 2007;Laranjo, Bernier, Meins, & Carlson, 2014;Slaughter, Peterson, & Carpenter, 2008)talking about past events in conversation (Lagattuta & Wellman, 2002;Laible, 2004;Laible & Thompson, 2000), meal preparation (Ensor & Hughes, 2008), mother to 'describe the child'(e.g. Lok & McMahon, 2006)or requesting a friend 'describe your friend (Hughes & Dunn, 1998) , pretend play (Dunn, Bretherton, & Munn, 1987;Hughes & Dunn, 1997) , wordless picture books and pictures (Baptista et al, 2017;Doan & Wang, 2010;Tarullo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similar is the case for Pakistani children. According to research done by Nawaz et al (2015), at the age of 5 years performance on theory of mind tasks is at chance, and these findings were replicated (Nawaz & Lewis, 2017). To fill this gap, one objective of the study is to explore at what age children in Pakistan achieve theory of mind development.…”
Section: Introductionmentioning
confidence: 99%